Solidarity and autonomy: two conflicting values in English and French health care and bioethics debates? - Gaille, M; Horn, R (Springer, 2016)
Although bioethics has had an international and universal outlook since its origin, divergent views on ethical questions in health care practice continue to exist across countries, even within the small continent of Europe. In the literature, the liberal approach of Anglo-American bioethics is often seen as opposed to the solidarity-based approach of continental European bioethics. Yet, despite the importance of recognising these different value systems, we believe that the opposition between Anglo-American and European bioethics does not capture the complexity of the situation. Bioethics and health care debates that take place in various countries influence each other and affect the way normative concepts are interpreted and used in different national contexts. If an international approach to bioethics is to be furthered and dialogue between countries improved, the meaning and use of dominant normative concepts in different countries needs to be better explored.